178 Long-term efficacy of ocrelizumab in relapsing multiple sclerosis. Issue 12 (14th November 2019) - Giovannoni, Gavin; Hauser, Stephen L; Brochet, Bruno; Montalban, Xavier; Naismith, Robert T; Wolinsky, Jerry S; Hubeaux, Stanislas; Mehta, Lahar; Model, Fabian; Kappos, Ludwig
Abstract : Background: The efficacy and safety of ocrelizumab in relapsing multiple sclerosis were demonstrated in the double-blind control period of the Phase III OPERA I/II trials (NCT01247324 /NCT01412333). Here we assessed the efficacy of switching to or maintaining ocrelizumab therapy after 3 years' follow-up in the open-label extensions (OLEs) of these studies. Methods: At OLE commencement, patients continued ocrelizumab (OCR-OCR) or switched from interferon-β-1a (IFN) to ocrelizumab (IFN-OCR). Adjusted annualised relapse rate (ARR) and time-to-onset of 24-week confirmed disability progression (CDP24) were analysed. Results: Among IFN-OCR patients, ARR decreased from 0.20 in the year pre-switch to 0.10, 0.08 and 0.07 at Years 1, 2 and 3 post-switch. OCR-OCR continuers maintained low ARRs through the year pre-OLE and the 3 years of OLE (0.13, 0.11, 0.08, 0.07). CDP24 was less frequent in OCR-OCR continuers versus IFN-OCR switchers in the year pre-switch and Years 1, 2 and 3 of OLE (7.7%/12.0%, 10.1%/15.6%, 13.9%/18.1% and 16.1%/21.3%; p<0.05, all comparisons). Conclusions: Switching from IFN to ocrelizumab at the start of the OLE provided rapid reductions in ARR, maintained throughout the 3-year follow-up. After 5 years' follow-up, patients who initiated ocrelizumab 2 years earlier accrued significant, sustained reductions in disability progression compared with patients switching from IFN. Disclosures: Sponsored by F. Hoffmann-La Roche Ltd; writing and editorial assistance was provided by Articulate Science, UK, and funded by F. Hoffmann-La Roche Ltd.